Challenges in Digital Social Research Methods: Algorithms, Traces and Footprints. A Resume of the Current Debate - Padricelli, Giuseppe Michele; Coppola, Marianna (Italian Sociological Review, 2024)
Nowadays, the digital scenario could be conceived as an extension of social reality where everything is real and where everyday life partly takes shape due to the cut of the online/offline duality in an always on world. Ascertained this premises, the role of the researcher and the readjustments of method and research techniques are as much as central. To focus them properly, it is necessary to take stock of the social objects central in social research and wonder with which native objects of the network can the researcher engage. What methodological itineraries and sets of techniques can be reconfigured to investigate social phenomena that extend within and beyond the network? What identification and operationalization procedures do they use to distinguish and categorize social objects appropriately taking care of the emerging of algorithms and digital traces? This paper proposes a reflection on the viable paths for the social researcher who must recognize the extensions of social reality within the Net today and inevitably grapple with its challenges. The reflection on limitations and methodological opportunities to overcome obstacles that arise in the researcher’s path are the insights properly evidenced in all the research papers contained in this issue.